Pengaruh Penggunaan Limbah Abu Sekam Padi dan Viscocrete 1003 Terhadap Kuat Tekan dan Kuat Lentur Beton: Pengaruh Penggunaan Limbah Abu Sekam Padi dan Viscocrete 1003 Terhadap Kuat Tekan dan Kuat Lentur Beton - Diana Ningrum; Nawir Rasidi; Hamdisuryaman Siritoitet (Universitas Islam Balitar Blitar, 2022)
The purpose of this study was to determine the effect of the use of waste rice husk ash and viscocrete 1003 on the compressive strength and flexural strength of concrete with variations in the mixture of rice husk ash waste 0%, 25%, 30% and viscocrete 1003 0.6%. The results showed that the chemical content of rice husk ash that had been burned was high SiO2 (Silicon Dioxide), which was 75.5 ─ 87.9 % by weight, while the chemical content of unburned rice husk ash was SiO2 (Silicon Dioxide). Which is high that is equal to 86.9 ─ 94.7% by weight. The compressive strength test value of each variation of the specimen which is converted into 28 days of age is for variation 0% the average compressive strength value is 21.590 MPa, for variation 25% with an average compressive strength value of 15.635 MPa and 30% variation with the average compressive strength value is 11.486 MPa. So it can be concluded that the average compressive strength value from the 0% variation to the 25% variation has decreased by 0.05955%, while from the 25% variation to the 30% variation it has decreased by 0.0415%. The flexural strength test value in terms of the maximum average moment on the slab for each variation of the test object converted into 28 days of age is for 0% variation of 146.820 kN.m, for 25% variation of 165.760 Kn.m and variation of 30% of 170.490 Kn.m. So it can be concluded that the average flexural strength value from the 0% variation to the 25% variation has increased by 3.13%, while from the 25% variation to the 30% variation it has increased by 3.36%.